Discussion on Some Problems of Bridge Scour in Both Experiment and Simulation. Issue 1 (January 2021) - Wang, Wei-zheng; Wei, Song; Duan, Haipeng; Cao, Jing; Jiang, Yuxi
Abstract: The scour of bridge piers is one of the important factors causing bridge damage. The research on the scour mechanism of bridge pier includes two main ways: physical experiment and numerical simulation. In this paper, the research progress in recent decades is summarized, and the influencing factors that include the Reynolds number, pier shape in physical experiments and the selection of models such as RANS, LES, DES in numerical simulation are sorted out. Both physical experiment and numerical simulation are used to investigate the depth of scour hole and flow structures. Finally, it is pointed out that the stress characteristics generated by scouring flow are one of the directions for further research.